2016
DOI: 10.1177/1756287216679946
|View full text |Cite
|
Sign up to set email alerts
|

Direct visual internal urethrotomy for isolated, post-urethroplasty strictures: a retrospective analysis

Abstract: Post-urethroplasty DVIU for isolated, recurrent strictures may be offered as a minimally invasive treatment option. Approximately 40% of patients were spared further intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…After urethroplasty recurrent strictures are mainly narrow fibrous rings at the anastomotic sites and usually due to existing pathology of the urethra, local ischaemia or defects in graft uptake [10] . The success rate for single DVIU for these strictures has been reported to be 35% with satisfactory outcomes [11] . Thus, in our present study, postoperative single intervention was considered to treat these ring strictures and was included in the definition of ‘success’.…”
Section: Discussionmentioning
confidence: 99%
“…After urethroplasty recurrent strictures are mainly narrow fibrous rings at the anastomotic sites and usually due to existing pathology of the urethra, local ischaemia or defects in graft uptake [10] . The success rate for single DVIU for these strictures has been reported to be 35% with satisfactory outcomes [11] . Thus, in our present study, postoperative single intervention was considered to treat these ring strictures and was included in the definition of ‘success’.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the literature supports this management strategy, with reported success rates of DVIU after urethroplasty higher than in primary USD and ranging from 34% to 60.5%. 11 , 21 , 49 , 50 The viability of endoscopic treatment for recurrent bulbar USD in particular is also supported by the OPEN trial with equivalent PROM measures after randomization to DVIU or urethroplasty. 47 Based on these data, it seems likely that many patients with recurrence after urethroplasty will benefit from endoscopic management as an initial attempt, particularly if the nature and extent of the stricture is assessed with imaging and/or cystoscopy and appears amenable to DVIU.…”
Section: Management Approachmentioning
confidence: 96%
“…[ 75 ] However, it has been clearly shown that the success rates after repeat urethroplasty are significantly higher compared to DVIU following urethroplasty, which do not exceed 40%–60%. [ 77 78 79 ] DVIU may be an adequate treatment option in cases of a short and focal stricture recurrence at the proximal or distal end of the former graft or EPA after open reconstruction. [ 80 ] Subtle differences could be shown in favor of DVIU after graft substitution compared to DVIU after EPA.…”
Section: Stricture Recurrencementioning
confidence: 99%